2014
DOI: 10.1186/2045-824x-6-13
|View full text |Cite
|
Sign up to set email alerts
|

In vitro pre-vascularisation of tissue-engineered constructs A co-culture perspective

Abstract: In vitro pre-vascularization is one of the main vascularization strategies in the tissue engineering field. Culturing cells within a tissue-engineered construct (TEC) prior to implantation provides researchers with a greater degree of control over the fate of the cells. However, balancing the diverse range of different cell culture parameters in vitro is seldom easy and in most cases, especially in highly vascularized tissues, more than one cell type will reside within the cell culture system. Culturing multip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
77
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(78 citation statements)
references
References 157 publications
(149 reference statements)
0
77
0
1
Order By: Relevance
“…25,26 Adding multiple cell types in an organoid presents a challenge regarding culture conditions. 27 In addition, in our system, culture conditions needed to be modified to sustain growth and differentiation of both cell types. We observed that endothelial cells fail to survive and form networks in the optimal culture condition for fibrin BAMs in skeletal muscle growth and differentiation medium.…”
Section: Discussionmentioning
confidence: 99%
“…25,26 Adding multiple cell types in an organoid presents a challenge regarding culture conditions. 27 In addition, in our system, culture conditions needed to be modified to sustain growth and differentiation of both cell types. We observed that endothelial cells fail to survive and form networks in the optimal culture condition for fibrin BAMs in skeletal muscle growth and differentiation medium.…”
Section: Discussionmentioning
confidence: 99%
“…The focus of this section is discussing the materials and microfabrication approaches to generate microvascular systems. Other review papers are recommended for detailed analyses of cell sources and biochemical modification of scaffolds (Bae, Puranik, 2012, Baldwin, Antille, 2014). …”
Section: Structural Mechanical and Microfabrication Considerationmentioning
confidence: 99%
“…Several literature reviews have largely focused on identifying critical aspects for successful development of vascularized models. Many of them were found to be mainly focused on the fundamental principles of engineering, microfabrication techniques (Auger et al, 2013) and microfluidic technologies (Inamdar and Borenstein, 2011, Wong et al, 2012), while other reviews highlighted the pivotal role of cell sources (Baldwin et al, 2014), scaffolds and pro-angiogenic factors (Bae et al, 2012, Kaully et al, 2009, Palumbo et al, 2014, Park and Gerecht, 2014) with low emphasis on microfabrication strategies. This review attempts to critically summarize and connect engineering principles and biological considerations as well as highlight how design of the system architecture and selection of the most suitable microfabrication technique are the first steps for analyzing biological phenomena occurring in a specific environment.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have indicated a positive effect of implanting biomaterial constructs co‐cultured with mesenchymal and vascular cells, where the development of vascularized tissues both in vitro and in vivo was enabled 25. Therefore, co‐culturing hMSCs with HUVECs in our study was conducted to generate the vascularized bone tissue.…”
Section: Resultsmentioning
confidence: 97%